2021
DOI: 10.1002/smll.202006599
|View full text |Cite
|
Sign up to set email alerts
|

A Virus‐Spike Tumor‐Activatable Pyroptotic Agent

Abstract: Invoking the occurrence of pyroptosis is an emerging strategy for the treatment of cancer. However, the practical applications of pyroptosis for cancer therapy are currently hindered due to the lack of tumor‐specific and efficient pyroptotic agents in vivo. Herein, a virus‐spike tumor‐activatable pyroptotic agent (VTPA) for cancer‐specific therapy is reported. The VTPA is composed of an organosilica coated iron oxide nanoparticle core and spiky manganese dioxide protrusions, which can readily accumulate in tum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(36 citation statements)
references
References 47 publications
0
36
0
Order By: Relevance
“…The lack of tumor-specific pyroptotic agents in vivo impedes the actual applications of pyroptosis-based cancer therapy. Nadeem et al reported the development of a virus-spike tumor-activatable pyroptotic agent (VTPA) for cancer-specific therapy 113 . The VTPA consists of a manganese dioxide spiky structure and an organosilica-coated iron oxide nanoparticle (IONP) core (Figure 5 A).…”
Section: Inducing Cancer Cell Pyroptosis For Cancer Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…The lack of tumor-specific pyroptotic agents in vivo impedes the actual applications of pyroptosis-based cancer therapy. Nadeem et al reported the development of a virus-spike tumor-activatable pyroptotic agent (VTPA) for cancer-specific therapy 113 . The VTPA consists of a manganese dioxide spiky structure and an organosilica-coated iron oxide nanoparticle (IONP) core (Figure 5 A).…”
Section: Inducing Cancer Cell Pyroptosis For Cancer Therapymentioning
confidence: 99%
“…(F) Tumor growth curves after different treatments. Adapted with permission from 113 , copyright 2021 John Wiley and Sons, and 114 , copyright 2021 John Wiley and Sons.…”
Section: Figurementioning
confidence: 99%
“…Reproduced with permission. [14] Copyright 2021, Wiley-VCH contrast agents are still in the proof-of-concept stage and several challenges remained to be addressed before further clinical application (Figure 6). First, oftentimes, there is only a slight physicochemical discrepancy between disease lesions and surrounding normal tissues, which puts forward high requirements on the sensitivity and selectivity of dynamic contrast agents (Figure 6).…”
Section:  Future Perspectivementioning
confidence: 99%
“…For example, our group designed a virus‐spike tumor‐activatable pyroptotic agent (VTPA) for dually switchable MRI‐guided cancer therapy, where organosilica coated IONP was synthesized as the core, which was further surface decorated with spiky manganese dioxide protrusions. [ 14 ] The spiky structure of VTPA can induce intracellular lysosomal rupture, and respond to tumor intracellular GSH to facilitate the effective release of Mn 2+ and IONP, eventually leading to the T1‐T2 dual MRI contrast enhancement and synergetic cancer pyroptosis (Figure 5E,F).…”
Section: Dynamically “T1 and T2” Dually Switchable Mri Contrast Agentmentioning
confidence: 99%
See 1 more Smart Citation